1999
DOI: 10.1063/1.477988
|View full text |Cite
|
Sign up to set email alerts
|

Average size and size distribution of large droplets produced in a free-jet expansion of a liquid

Abstract: The experimental parameters and fluid properties affecting the average size N̄ and the size distribution P(N) of droplets formed by fragmentation of a liquid after expansion into a vacuum are investigated. The mean droplet size is found to be a function of the surface tension of the liquid, the nozzle diameter, and a characteristic flow speed. The size distribution is found to be a linear exponential distribution; measurements deviate from this distribution at small sizes if a factor which is a function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 16 publications
3
61
1
2
Order By: Relevance
“…Theoretically, it cannot be excluded that this signal stems from a contamination of the droplet beam by isolated helium atoms or from background helium gas in the experimental chamber. However, from measured cluster size distributions 54,55 we do not expect a significant contribution of atoms in the cluster beam. Furthermore, the PAD generated by the 17th harmonic leakage of the multilayer mirror is isotropic (not shown), which indicates that there is no prominent contribution of isolated helium atoms in the interaction volume that would otherwise produce an anisotropic PAD corresponding to an outgoing p-wave from direct He1s ionization.…”
Section: Atomic Rydberg Statesmentioning
confidence: 80%
“…Theoretically, it cannot be excluded that this signal stems from a contamination of the droplet beam by isolated helium atoms or from background helium gas in the experimental chamber. However, from measured cluster size distributions 54,55 we do not expect a significant contribution of atoms in the cluster beam. Furthermore, the PAD generated by the 17th harmonic leakage of the multilayer mirror is isotropic (not shown), which indicates that there is no prominent contribution of isolated helium atoms in the interaction volume that would otherwise produce an anisotropic PAD corresponding to an outgoing p-wave from direct He1s ionization.…”
Section: Atomic Rydberg Statesmentioning
confidence: 80%
“…This is a hint that ablation might have a mechanical origin in this case. Indeed, separation of supercritical fluids subject to important strain rates into small clusters has been observed before in numerous situations: computer simulation of two and threedimensional Lennard-Jones systems under homogeneous expansion [28] and of rapid heating of liquid drops [29,30], experiments on the free-jet expansion of liquids [31,32], etc. This process is called fragmentation.…”
Section: Fragmentationmentioning
confidence: 83%
“…In [15], it was shown that both 3D MD results with a homogeneous strain rate η and data from helium free jets experiments from [33] could be fitted to Eq. 1 with the same prefactor, thus validating this law over almost 8 orders of magnitude in cluster mass (the experimental fragments cover larger sizes than the numerical ones).…”
Section: B Initial Droplet Sizementioning
confidence: 99%